2005
DOI: 10.1128/jvi.79.7.4415-4424.2005
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Transforming Protein LMP1 Plays a Critical Role in Virus Production

Abstract: The Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1), which is critical for EBV-induced B-cell transformation, is also abundantly expressed during the lytic cycle of viral replication. However, the biological significance of this strong LMP1 induction remains unknown. We engineered a bacterial artificial chromosome clone containing the entire genome of Akata strain EBV to specifically disrupt the LMP1 gene. Akata cell clones harboring the episomes of LMP1-deleted EBV were established, and the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…In a previous study, lack of LMP1 expression severely impaired virus release into culture supernatants, which resulted in poor infection efficiency. These results have suggested that LMP1 serves an important role in EBV particle release from cells during the lytic cycle and in the infection of new host cells (46). Furthermore, a different study identified that low expression of LMP1 suppressed the activity of the EBV latent replication origin oriP, and that the LMP1 binding site for tumor necrosis factor receptor-associated factor was essential for this suppressive effect (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, lack of LMP1 expression severely impaired virus release into culture supernatants, which resulted in poor infection efficiency. These results have suggested that LMP1 serves an important role in EBV particle release from cells during the lytic cycle and in the infection of new host cells (46). Furthermore, a different study identified that low expression of LMP1 suppressed the activity of the EBV latent replication origin oriP, and that the LMP1 binding site for tumor necrosis factor receptor-associated factor was essential for this suppressive effect (49).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that LMP1 serves an important role in the EBV lytic cycle (24,45,46). While LMP1 may be expressed in some states of EBV latency, significant induction of full-length LMP1 is frequently observed during virus reactivation into the lytic cycle (13,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Culture supernatants were prepared from cell clone harboring d.LMP1-EBV [16] and used to infect peripheral B cells. The culture supernatant containing AK-BAC-GFP virus [15] was also used for another infection as a control.…”
Section: Results: Dlmp1-ebv and Ak-bac-gfp Showed Similar Infection mentioning
confidence: 99%
“…We previously constructed a recombinant Akata strain EBV as AK-BAC-GFP that had a GFP gene in their genome 15 and d.LMP1-EBV by using AK-BAC-GFP as the starting material for mutagenesis [16] . This d.LMP1-EBV also expressed all viral genes except LMP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation